Helicobacter pylori and Gastric Metaplasia: Their Status after Eradication Therapy (TAJ: Journal of Teachers Association, 2009)
This study was carried out with an aim to investigate the relationship between gastricmetaplasia with H. pylori and the effect of eradication therapy. A total of 210 patients withhistory of dyspepsia were included in the study of which 50 were enrolled in the eradicationtherapy. After the eradication therapy 35 patients came for follow-up endoscopy. Pairedendoscopic biopsies were taken from antrum and duodenal ulcer margin and were examined forH. pylori and for duodenitis and gastric metaplasia. Gastric metaplasia was significantlyassociated with H. pylori. After eradication H. pylori showed further extension of gastricmetaplasia. It can be recommended that these patients can be further followed up to see thecourse of gastric metaplasia and what impact it has on ulcer recurrence and re-infection.doi: 10.3329/taj.v15i2.3908TAJ December 2002; Vol.15(2):59-63